Reconstruction of downhole fluid dynamics: Performance comparison of multiple vortex tool types - Tianyue Guo; Bin Huang; Daye Wang; Cheng Fu; Yu Sui (Results in Engineering)
The issue of liquid accumulation at the bottom of natural gas wells poses a critical bottleneck for efficient production and extended well lifespan. To address this challenge, this study innovatively developed the three-lobed variable-diameter vortex tool and systematically compared its gas-liquid two-phase flow characteristics with the internal vortex tool, three-lobed obtuse-angle vortex, and three-lobed acute-angle vortex through numerical simulations. Results indicate that the three-lobed variable-diameter vortex tool demonstrates outstanding performance in gas-liquid separation, effectively transforming dispersed flow into annular flow and forming a uniform and continuous liquid film. The liquid film parameters, ranked in ascending order, are as follows: three-lobed vortex obtuse-angle tool < internal vortex tool < three-lobed vortex acute-angle tool < three-lobed variable-diameter vortex tool. The average thickness, perimeter, and area of the liquid film in the three-lobed variable-diameter vortex tool reach 1.35 mm, 189.02 mm, and 246 mm², respectively. Although the acceleration induced by the three-lobed variable-diameter vortex tool results in a greater pressure drop (10.6 %), it achieves a maximum velocity of 83.2 m/s and maintains a more stable velocity core, significantly outperforming other tools. The design of the three-lobed variable-diameter vortex tool introduces a novel approach to gas well drainage gas recovery, showcasing tremendous potential for extending well lifespan and enhancing gas production efficiency.